Culture and Counterfactuals: On the Importance of Life Domains - CHEN, Jing (Institutional Knowledge at Singapore Management University, 2006)
Past research, with its emphasis on affective regulatory processes, has failed to find cross-cultural differences in counterfactual thoughts. In the current study, the authors examine the tendency to generate additive counterfactuals (those that focus on the addition of new aspects that were not in fact present) and subtractive counterfactuals (those that focus on subtraction of factual aspects) among Mainland Chinese and European American university students in five life domains: schoolwork, romantic relationships, family relationships, friendships, and life in general. As in previous studies, the authors find an overall main effect, in which additive counterfactuals predominate over subtractive counterfactuals within both cultural groups. However, they also find systematic cultural differences in the likelihood of generating additive and subtractive counterfactuals in the domains of schoolwork and family. These findings are discussed in terms of their implications for understanding the nature of cultural differences.